Mono-lateral external fixation for treatment of femoral osteomyelitis - Mohd Yusof, Nazri; Saleh, Ayman K; Abuomira, Ibrahim Elsayed Abdellatif A; Attallah, Abdehamid A; Elshal, Ehab Abdelftah; Khames, Amr Abdelhalem Amr (Dove Medical Press, 2022)
Background and Aim: Maintenance of stability using external fixation devices is an important principle to ensure successful treatment of osteomyelitis (OM). In this study, we report our experience with femoral OM treated with acute compression and bone transport using the Orthofix limb reconstruction system (LRS). Patients and Methods: This prospective study included 30 consecutive patients with femoral OM. LRS insertion and corticotomy were done according to the standard technique. Radiographic evaluation was performed every 2 weeks during the distraction phase and every 2–4 weeks during the consolidation phase. The clinical outcome measurements included union time, limb length discrepancy, additional operative procedures, refracture and infection. Results: The present study included 30 patients with femoral OM. They comprised 27 males (90.0%) and 3 females (10.0%) with an age of 28.1 ± 15.6 years. All, except one, achieved union with a mean union time of 8.6 months (range 4–20 months). The mean union time for acute compression was 7.6 months (range 4–20 months) while for patients with bone transport it was 14.5 months (range 12–18 months). The mean limb length discrepancy was 1.8 cm (range 0–4 cm). At the end of the follow=up, two patients were not able to ambulate without support; one due to non-union and one due to paraplegia. Conclusion: The present study identified treatment of femoral OM using LRS as a feasible and effective technique with good outcomes. Reported complications could be adequately managed in most cases